Answer:
Proved that [tex](\tan \theta + \cot \theta)^{2} = \sec^{2} \theta + \csc^{2} \theta[/tex].
Step-by-step explanation:
We have to prove that
[tex](\tan \theta + \cot \theta)^{2} = \sec^{2} \theta + \csc^{2} \theta[/tex]
Now, Left hand side
= [tex](\tan \theta + \cot \theta)^{2}[/tex]
= [tex]\tan^{2} \theta + 2\times \tan \theta \times \cot \theta + \cot^{2} \theta[/tex] {Since we know the formula (a + b)² = a² + 2ab + b²}
= [tex]\tan^{2} \theta + 2 + \cot^{2} \theta[/tex]
{Since [tex]\tan \theta \times \cot \theta = 1[/tex]}
= [tex](\tan^{2} \theta + 1) + (\cot^{2} \theta + 1)[/tex]
= [tex]\sec^{2} \theta + \csc^{2} \theta[/tex]
{Since we know the identities:
[tex]\sec^{2} x = \tan^{2} x + 1[/tex] and [tex]\csc^{2} x = \cot^{2} x + 1[/tex]}
= Right hand side
Hence, proved.